Influence of mechanical and chemical degradation in the surface roughness, gloss, and color of microhybrid composites - Lemos, Cleidiel A.A. [UNESP]; Mauro, Silvio José [UNESP]; Santos, Paulo Henrique dos [UNESP]; Briso, André Luiz Fraga [UNESP]; Fagundes, Ticiane Cestari [UNESP] (Jaypee Brothers Medical Publishing, 2017)
Aim: The aim of this study was to investigate the association of different degradations on the roughness, gloss, and color changes of microhybrid composites. Materials and methods: Ten specimens were prepared for Charisma, Amelogen Plus, Point 4, and Opallis resins. Surfaces were polished and baseline measurements of roughness, gloss, and color were recorded. Specimens were then submitted to chemical and mechanical challenges, and the specimens were reevaluated. Roughness and gloss were analyzed by Kruskal - Wallis and Dunn's test (p < 0.05). Color change (AE) was analyzed by one-way analysis of variance and Tukey's tests (p < 0.05). The initial and final data were compared using the Wilcoxon test (p < 0.05). Spearman test checked the correlation between the roughness and gloss (p < 0.05). Results: Regarding surface roughness and gloss, there was no difference between composites before challenges. However, all composites showed a significant increase of roughness after challenges, with highest values for Charisma. The gloss was influenced by challenges, evidencing the best gloss for Point 4. Charisma showed the highest value of color change. There was no correlation between surface roughness and gloss for the initial analysis, and after the challenges. Conclusion: Composites were influenced by association of challenges, and Charisma showed the highest changes for roughness, gloss, and color. Clinical significance: The type of composite resin influenced the properties of materials, which are surface roughness, gloss, and color change. The dentist should be aware of the performance of different brands, to choose the correct required composite resin for each type of patient or region to be restored.
Keywords: Chemical degradation; Composite resins; Esthetics; Physical properties; Toothbrushing